Acrylic Emulsion
An acrylic emulsion with a controlled particle size of 150 nm to 300 nm, containing specific structural units, addresses stability and coagulation issues in acrylic rubber production, resulting in improved product quality.
Patent Information
- Application Number
- JP2021551262
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-30
- Filing Date
- 2020-09-28
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-09-28
AI Technical Summary
Existing acrylic emulsion polymerization methods lack emulsion stability and efficient coagulation properties, which affect the production process of acrylic rubber.
The development of an acrylic emulsion with a specific particle size range of 150 nm to 300 nm, containing structural units derived from (meth)acrylic acid esters and unsaturated monomers with crosslinking groups, enhances coagulation properties and stability.
The acrylic emulsion exhibits improved coagulation properties and stability, ensuring consistent production of high-quality acrylic rubber with enhanced properties.
Smart Images

Figure 0007600995000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an acrylic emulsion for producing an acrylic rubber. [Background technology]
[0002] In general, acrylic rubber is a polymer made primarily from acrylic esters and is known as a material with excellent physical properties related to durability. It is widely used as an industrial rubber material, such as for engine gaskets, oil hoses, air hoses, and O-rings, as well as an automotive rubber material.
[0003] The acrylic rubber is obtained through a process including the steps of obtaining an emulsion polymerization liquid by emulsion polymerizing a monomer, coagulating the emulsion polymerization liquid with a coagulant, and drying the coagulated slurry obtained by coagulation.
[0004] In the method for producing acrylic rubber, the production conditions for each step have been investigated (see Patent Document 1). However, little research has been done on the emulsion polymerization liquid (acrylic emulsion) obtained by emulsion polymerizing the monomers for producing acrylic rubber. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] WO2018 / 147142 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide an emulsion that has excellent coagulation properties (salting-out properties) and stability. [Means for solving the problem]
[0007] As a result of extensive investigations into the above-mentioned problems, the present inventors have found that the above-mentioned problems can be achieved by preparing an acrylic emulsion containing an acrylic polymer having an average particle size of 150 nm to 300 nm in the step of emulsion polymerization of monomers in the production of acrylic rubber, and have thus completed the present invention.
[0008] The aspects of the present invention are as follows. Item 1: An acrylic emulsion containing an acrylic polymer having an average particle size of 150 nm to 300 nm, the acrylic polymer containing a structural unit derived from a (meth)acrylic acid ester and a structural unit derived from an unsaturated monomer having a crosslinking group. Item 2. An acrylic rubber produced using the acrylic emulsion according to item 1. Item 3. An acrylic rubber-containing composition comprising the acrylic rubber according to item 2 and a crosslinking agent. Item 4. An acrylic rubber cross-linked product produced by using the acrylic rubber-containing composition according to item 3. Item 5. A step of coagulating the acrylic emulsion according to Item 1 with a coagulant to obtain a coagulated slurry; A step of obtaining an acrylic rubber by drying the solidified slurry; The method for producing acrylic rubber comprises the steps of: Effect of the Invention
[0009] According to the present invention, by controlling the average particle size of the acrylic polymer in the emulsion to fall within the range of 150 nm to 300 nm, excellent coagulation properties in the production of acrylic rubber and excellent emulsion stability can be achieved, resulting in an emulsion with excellent stability during liquid delivery in the production process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Acrylic Emulsion The acrylic emulsion of the present invention is an acrylic polymer (acrylic fine particles) containing a constituent unit derived from a (meth)acrylic acid ester and a constituent unit derived from an unsaturated monomer having a crosslinking group, and having an average particle size of 150 nm to 300 nm, dispersed in water. The "average particle size" refers to the particle size (D50 particle size) corresponding to a cumulative 50% in the volume-based particle size distribution measured by a light scattering method. The average particle size can be measured by a dynamic light scattering method, and a dynamic light scattering device (such as "Zetasizer Nano S") can be exemplified.
[0011] The acrylic polymer of the present invention contains a structural unit derived from a (meth)acrylic acid ester and a structural unit derived from an unsaturated monomer having a crosslinking group.
[0012] Examples of the structural unit derived from the (meth)acrylic acid ester include a structural unit derived from an alkyl (meth)acrylic acid ester and a structural unit derived from an alkoxyalkyl (meth)acrylic acid ester. The structural unit derived from an alkyl acrylate having an alkyl group having 1 to 8 carbon atoms and the structural unit derived from an alkoxy acrylate having an alkoxyalkyl group having 2 to 8 carbon atoms are preferable. The structural unit derived from an alkyl acrylate having an alkyl group having 2 to 6 carbon atoms and / or the structural unit derived from an alkoxyalkyl acrylate having an alkoxyalkyl group having 2 to 6 carbon atoms are more preferable. The structural unit derived from the (meth)acrylic acid ester may be a single structural unit or two or more structural units derived from a (meth)acrylic acid ester.
[0013] Specific examples of (meth)acrylic acid alkyl esters include (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and cyclohexyl (meth)acrylate, of which ethyl (meth)acrylate and n-butyl (meth)acrylate are preferred. Specific examples of the (meth)acrylic acid alkoxyalkyl ester include (meth)acrylic acid esters such as methoxymethyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxymethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-propoxyethyl (meth)acrylate, 2-butoxyethyl (meth)acrylate, 2-methoxypropyl (meth)acrylate, 2-ethoxypropyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, and 4-ethoxybutyl (meth)acrylate, with methoxyethyl (meth)acrylate being preferred.
[0014] The content of structural units derived from (meth)acrylic acid ester in the acrylic rubber of the present invention is more preferably 50 mass% or more, and particularly preferably 60 mass% or more, of all structural units of the acrylic rubber, and the upper limit is preferably 99.5 mass% or less, more preferably 99 mass% or less, and particularly preferably 98.5 mass% or less.
[0015] The acrylic polymer of the present invention contains a structural unit derived from an unsaturated monomer having a crosslinking group.As the structural unit derived from an unsaturated monomer having a crosslinking group, the structural unit derived from an unsaturated monomer having a halogen group (e.g., chlorine group, etc.), the structural unit derived from an unsaturated monomer having a carboxyl group, and the structural unit derived from an unsaturated monomer having an epoxy group can be exemplified, and the structural unit derived from an unsaturated monomer having a halogen group (especially chlorine group) and the unsaturated monomer having a carboxyl group is particularly preferred.
[0016] Examples of the unsaturated monomer having a halogen group include 2-chloroethyl vinyl ether, 2-chloroethyl acrylate, vinylbenzyl chloride, vinyl monochloroacetate, and allyl chloroacetate.
[0017] Examples of the unsaturated monomer having a carboxy group include unsaturated monocarboxylic acids such as (meth)acrylic acid, crotonic acid, 2-pentenoic acid, and cinnamic acid, unsaturated dicarboxylic acids such as fumaric acid, maleic acid, and itaconic acid, carboxylic anhydrides such as maleic anhydride and citraconic anhydride, butenedioic acid mono-chain alkyl esters such as monomethyl fumarate, monoethyl fumarate, mono-n-butyl fumarate, monomethyl maleate, monoethyl maleate, mono-2-ethylhexyl maleate, and mono-n-butyl maleate, butenedioic acid mono-cyclic alkyl esters such as monocyclopentyl fumarate, monocyclohexyl fumarate, monocyclopentyl maleate, and monocyclohexyl maleate, and itaconic acid monoesters such as monomethyl itaconate, monoethyl itaconate, mono-n-butyl itaconate, and monocyclohexyl itaconate. Among these, there may be mentioned unsaturated dicarboxylic acid monoesters such as monoethyl fumarate, monopropyl fumarate, monobutyl fumarate, monoethyl itaconate, monopropyl itaconate, and monobutyl itaconate.
[0018] Examples of the unsaturated monomer having an epoxy group include glycidyl (meth)acrylate and (meth)allyl glycidyl ether.
[0019] The content of the structural units derived from the unsaturated monomer having a crosslinking group in the acrylic polymer is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, particularly preferably 0.5% by mass or more, and preferably 10% by mass or less, more preferably 5% by mass or less, particularly preferably 3% by mass or less, based on the total structural units of the acrylic polymer. The above range of the structural units derived from the unsaturated monomer having a crosslinking group is preferable in terms of the physical properties such as the strength and compression set of the acrylic rubber produced, and the processability.
[0020] Furthermore, the acrylic polymer of the present invention may contain, in addition to the above-mentioned structural units, structural units derived from other monomers copolymerizable therewith. Examples of the other structural units include structural units derived from ethylenically unsaturated nitriles, structural units derived from (meth)acrylamide monomers, structural units derived from aromatic vinyl monomers, structural units derived from conjugated diene monomers, structural units derived from non-conjugated dienes, structural units derived from other olefins, etc.
[0021] Examples of the ethylenically unsaturated nitrile include compounds such as acrylonitrile, methacrylonitrile, α-methoxyacrylonitrile, and vinylidene cyanide.
[0022] Examples of the (meth)acrylamide monomer include acrylamide, methacrylamide, diacetone acrylamide, diacetone methacrylamide, N-butoxymethyl acrylamide, N-butoxymethyl methacrylamide, N-butoxyethyl acrylamide, N-butoxyethyl methacrylamide, N-methoxymethyl acrylamide, N-methoxymethyl methacrylamide, N-propioxymethyl acrylamide, N-propioxymethyl methacrylamide, N-methyl acrylamide, N-methyl methacrylamide, N,N-dimethyl acrylamide, N,N-dimethyl methacrylamide, N,N-diethyl acrylamide, N,N-diethyl methacrylamide, N-methylolacrylamide, N-methylol methacrylamide, ethacrylamide, crotonamide, cinnamic acid amide, maleindiamide, itacondiamide, methylmaleamide, methyl itaconamide, maleimide, itaconimide, and other compounds.
[0023] Examples of aromatic vinyl monomers include compounds such as styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, o-ethylstyrene, p-ethylstyrene, α-fluorostyrene, p-trifluoromethylstyrene, p-methoxystyrene, p-aminostyrene, p-dimethylaminostyrene, p-acetoxystyrene, styrenesulfonic acid or a salt thereof, α-vinylnaphthalene, 1-vinylnaphthalene-4-sulfonic acid or a salt thereof, 2-vinylfluorene, 2-vinylpyridine, 4-vinylpyridine, divinylbenzene, diisopropenylbenzene, and vinylbenzyl chloride.
[0024] Examples of conjugated diene monomers include compounds such as 1,3-butadiene, 2-methyl-1,3-butadiene, 2-chloro-1,3-butadiene, 1,2-dichloro-1,3-butadiene, 2,3-dichloro-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-neopentyl-1,3-butadiene, 2-bromo-1,3-butadiene, 2-cyano-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, chloroprene, and piperylene.
[0025] Examples of structural units derived from non-conjugated dienes include structural units derived from non-conjugated diene compounds such as 1,4-pentadiene, 1,4-hexadiene, ethylidenenorbornene, norbornadiene, and dicyclopentadiene.
[0026] Other olefin monomers include esters such as dicyclopentadienyl acrylate, dicyclopentadienyl methacrylate, dicyclopentadienyl ethyl acrylate, and dicyclopentadienyl ethyl methacrylate, as well as compounds such as ethylene, propylene, vinyl chloride, vinylidene chloride, 1,2-dichloroethylene, vinyl acetate, vinyl fluoride, vinylidene fluoride, 1,2-difluoroethylene, vinyl bromide, vinylidene bromide, 1,2-dibromoethylene, ethyl vinyl ether, and butyl vinyl ether.
[0027] When the acrylic polymer of the present invention contains structural units derived from these other copolymerizable monomers, the content of the total structural units is usually 0 to 45 mass %, and preferably 0 to 20 mass %.
[0028] The water in which the acrylic polymer is dispersed in the acrylic emulsion of the present invention is not particularly limited, and any commonly used water can be used, specific examples of which include tap water, pure water, distilled water, ion-exchanged water, and ultrapure water.
[0029] The content of the acrylic polymer in the acrylic emulsion of the present invention is preferably such that the solid content concentration in solids other than water (hereinafter simply referred to as "solids") is 5 to 80 mass%, more preferably 10 to 70 mass%, and particularly preferably 15 to 60 mass%.
[0030] The acrylic emulsion of the present invention can be an emulsion polymerization liquid obtained by emulsion polymerization of a (meth)acrylic acid ester (monomer) and an unsaturated monomer having a crosslinking group.
[0031] When the acrylic emulsion of the present invention is obtained as an emulsion polymerization liquid, it can be obtained by emulsion polymerizing a monomer (also referred to as an emulsion polymerization step), and the emulsifier, polymerization initiator, chain transfer agent, polymerization terminator, and the like used in the emulsion polymerization can be any commonly used conventionally known agent.
[0032] The emulsifier is not particularly limited, and nonionic emulsifiers and anionic emulsifiers that are generally used in emulsion polymerization methods can be used. Examples of nonionic emulsifiers include polyoxyethylene alkyl ethers, polyoxyethylene alcohol ethers, polyoxyethylene alkyl phenyl ethers, polyoxyethylene polycyclic phenyl ethers, polyoxyalkylene alkyl ethers, sorbitan fatty acid esters, polyoxyethylene fatty acid esters, and polyoxyethylene sorbitan fatty acid esters. Examples of anionic emulsifiers include alkylbenzene sulfonates, alkyl sulfates, polyoxyethylene alkyl ether sulfates, polyoxyalkylene alkyl ether phosphates or their salts, polyoxyalkylene alkyl phenyl ether phosphates or their salts, and fatty acid salts. Examples of salts include alkali metals such as sodium and potassium, ammonia, and amines. These may be used alone or in combination.
[0033] The amount of the emulsifier used may be an amount generally used in emulsion polymerization. Specifically, it is in the range of 0.01 to 10% by mass, preferably 0.03 to 7% by mass, and more preferably 0.05 to 5% by mass, based on the amount of the charged monomer. When a reactive surfactant is used as the monomer component, the addition of an emulsifier is not necessarily required.
[0034] The polymerization initiator is not particularly limited, and a polymerization initiator generally used in emulsion polymerization can be used. Specific examples thereof include inorganic polymerization initiators such as persulfates, such as potassium persulfate, sodium persulfate, and ammonium persulfate, 2,2-di(4,4-di(t-butylperoxy)cyclohexyl)propane, 1-di(t-hexylperoxy)cyclohexane, 1,1-di(t-butylperoxy)cyclohexane, 4,4-di(t-butylperoxy)n-butyl valerate, 2,2-di(t-butylperoxy)butane, t-butyl hydroperoxide, and cumene hydroperoxide. Side, diisopropylbenzene hydroperoxide, p-menthane hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, t-butylcumyl peroxide, di-t-butyl peroxide, di-t-hexyl peroxide, di(2-t-butylperoxyisopropyl)benzene, dicumyl peroxide, diisobutyryl peroxide, di(3,5,5-trimethylhexanoyl) peroxide, dilauroyl peroxide, disuccinic acid peroxide peroxydicarbonate, dibenzoyl peroxide, di(3-methylbenzoyl) peroxide, benzoyl(3-methylbenzoyl) peroxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(4-t-butylcyclohexyl) peroxydicarbonate, di(2-ethylhexyl) peroxydicarbonate, di-sec-butyl peroxydicarbonate, cumyl peroxyneodecanate, 1,1,3,3-tetramethylbutyl peroxyneodecanate Canate, t-hexylperoxyneodecanate, t-butylperoxyneodecanate, t-hexylperoxypivalate, t-butylperoxypivalate, 2,5-dimethyl-2,5-di(2-ethylhexanoylperoxy)hexane, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanate, t-hexylperoxy-2-ethylhexanate, t-butylperoxy-2-ethylhexanate, t-butylperoxylaurate, t-butylperoxy-3,5,Polymerization initiators of organic peroxides such as 5-trimethylhexanate, t-hexylperoxyisopropyl monocarbonate, t-butylperoxyisopropyl monocarbonate, t-butylperoxy2-ethylhexyl monocarbonate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, t-butylperoxyacetate, t-hexylperoxybenzoate, t-butylperoxybenzoate, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, hydroperoxides, azobisisobutyronitrile, 4-4'-azobis(4- Examples of the azo initiator include 2-2'-azobis[2-(2-imidazolin-2-yl)propane, 2-2'-azobis(propane-2-carboxamidine), 2-2'-azobis[N-(2-carboxyethyl)-2-methylpropanamide, 2-2'-azobis{2-[1-(2-hydroxyethyl)-2-imidazolin-2-yl]propane}, 2-2'-azobis(1-imino-1-pyrrolidino-2-methylpropane) and 2-2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propanamide}. These polymerization initiators may be used alone or in combination of two or more.
[0035] The amount of the polymerization initiator used may be an amount generally used in emulsion polymerization, specifically, in the range of 0.01 to 5% by mass, preferably 0.01 to 4% by mass, and more preferably 0.02 to 3% by mass, based on the amount of the charged monomer.
[0036] In addition, the organic peroxide and inorganic peroxide as the polymerization initiator can be used as a redox polymerization initiator by combining with a reducing agent. The reducing agent to be used in combination is not particularly limited, but includes compounds containing metal ions in a reduced state such as ferrous sulfate and cuprous naphthenate, methane compounds such as sodium methanesulfonate, amine compounds such as dimethylaniline, ascorbic acid and its salts, and inorganic salts having reducing properties such as alkali metal salts of sulfurous acid and thiosulfate. These reducing agents can be used alone or in combination of two or more. The amount of the reducing agent used is preferably 0.0001 to 10.0 parts by mass relative to 100 parts by mass of the charged monomer.
[0037] A molecular weight regulator can be used as necessary. Specific examples of the molecular weight regulator include alkyl mercaptans such as n-hexyl mercaptan, n-octyl mercaptan, t-octyl mercaptan, n-dodecyl mercaptan, t-dodecyl mercaptan, and n-stearyl mercaptan, xanthogen compounds such as 2,4-diphenyl-4-methyl-1-pentene, 2,4-diphenyl-4-methyl-2-pentene, dimethyl xanthogen disulfide, and diisopropyl xanthogen disulfide, terpinolene, tetramethylthiuram disulfide, tetraethylthiuram disulfide, and tetramethylthiuram monosulfide. Thiuram compounds, phenolic compounds such as 2,6-di-t-butyl-4-methylphenol and styrenated phenol, allyl compounds such as allyl alcohol, halogenated hydrocarbon compounds such as dichloromethane, dibromomethane and carbon tetrabromide, vinyl ethers such as α-benzyloxystyrene, α-benzyloxyacrylonitrile and α-benzyloxyacrylamide, triphenylethane, pentaphenylethane, acrolein, methacrolein, thioglycolic acid, thiomalic acid, 2-ethylhexyl thioglycolate, etc., may be used alone or in combination. The amount of these molecular weight regulators is not particularly limited, but is usually 0 to 5 parts by mass per 100 parts by mass of the charged monomer.
[0038] Examples of the polymerization terminator include hydroxylamine, hydroxylamine sulfate, diethylhydroxyamine, hydroxylamine sulfonic acid and its alkali metal salts, sodium dimethyldithiocarbamate, and quinone compounds such as hydroquinone. The amount of the polymerization terminator used is not particularly limited, but is usually 0 to 2 parts by mass relative to 100 parts by mass of the total monomers.
[0039] In addition, polymerization secondary materials such as particle size regulators, chelating agents, and oxygen scavengers can be used as necessary.
[0040] The emulsion polymerization may be any of batch, semi-batch, and continuous. The polymerization time and temperature are not particularly limited. They can be appropriately selected depending on the type of polymerization initiator used, but generally, the polymerization temperature is 10 to 100°C, and the polymerization time is 0.5 to 100 hours.
[0041] The method for adjusting the particle size of the acrylic polymer is not particularly limited, but it can be adjusted by the type and amount of emulsifier, the ratio of water to monomer, stirring conditions during polymerization, and the like.
[0042] The viscosity of the acrylic emulsion of the present invention (at 25°C) is preferably 7.0 to 20.0 mPa·s, and more preferably 7.5 to 15.0 mPa·s, in order to provide excellent coagulation (salting out) properties and stability. The viscosity of the acrylic emulsion is a value measured in accordance with JIS K7117-1 at 23°C using a commercially available rotational viscometer (e.g., Brookfield, manufactured by Eiko Seiki Co., Ltd.) with an LV-1 spindle at a rotation speed of 30 rpm.
[0043] The acrylic emulsion of the present invention can be coagulated with a coagulant to form a coagulated slurry, and the coagulated slurry can be dried to obtain an acrylic rubber.
[0044] The process of solidifying the acrylic emulsion (emulsion polymerization liquid obtained in the emulsion polymerization process) of the present invention with a coagulant will be described below. Hereinafter, it may also be referred to as the solidification process.
[0045] The coagulant used in the coagulation step is not particularly limited, but is preferably an inorganic metal salt, specific examples of which include sodium sulfate, magnesium sulfate, aluminum sulfate, sodium chloride, and calcium chloride.
[0046] The method of coagulation by a coagulant is not particularly limited, and a commonly used method can be adopted. One example of the method is to continuously or batchwise supply an acrylic emulsion (emulsion polymerization liquid) to an aqueous solution containing a coagulant, and a coagulated slurry is obtained by this operation. At that time, the temperature of the aqueous solution containing the coagulant is affected by the type and amount of monomer used, shear force due to stirring, etc., so it cannot be uniformly specified, but it is generally 50°C or higher, preferably in the range of 60°C to 100°C.
[0047] The coagulated slurry obtained by the above method is preferably washed with water to remove the coagulant. Hereinafter, this may be referred to as the washing step. If washing with water is not performed at all or is insufficient, there is a risk that ion residues derived from the coagulant will be precipitated during the molding step.
[0048] The step of drying the solidified slurry obtained by solidification will be described below. Hereinafter, this step may also be referred to as the drying step.
[0049] The solidified slurry is dried to remove water, thereby obtaining an acrylic rubber. The drying method is not particularly limited, but is generally carried out using a flash dryer or a fluidized bed dryer.
[0050] The drying temperature is not particularly limited, but is preferably 50 to 200° C., and more preferably 80 to 200° C. The drying time varies depending on the drying temperature.
[0051] Before the drying step, a dehydration step using a centrifuge or the like may be performed.
[0052] The molecular weight range of the acrylic rubber used in the present invention is set to be within the Mooney viscosity (ML 1+4 ) is preferably 10 to 100, more preferably 15 to 90, and even more preferably 20 to 80.
[0053] The method for producing acrylic rubber using the acrylic emulsion of the present invention includes the following steps: The process includes an emulsion polymerization step of obtaining an emulsion polymerization liquid (acrylic emulsion) by emulsion polymerization of monomers, a coagulation step of coagulating the emulsion polymerization liquid with a coagulant to obtain a coagulated slurry, and a drying step of drying the water-containing crumbs. It can also be described as a method for producing acrylic rubber, characterized in that the emulsion polymerization liquid (acrylic emulsion) contains a constituent unit derived from a (meth)acrylic acid ester and a constituent unit derived from an unsaturated monomer having a crosslinking group, and contains an acrylic polymer having an average particle size of 150 nm to 300 nm.
[0054] <Acrylic rubber-containing composition> The acrylic rubber-containing composition of the present invention contains at least the above-mentioned acrylic rubber and a crosslinking agent.
[0055] As the crosslinking agent, a conventionally known crosslinking agent that is usually used for crosslinking rubber, such as a polyamine compound, a polyepoxy compound, a polyisocyanate compound, an aziridine compound, a sulfur compound, a thiol compound, a higher fatty acid metal salt (fatty acid metal soap), etc., can be used. Among these, a polyamine compound is preferably used.
[0056] Examples of the polyamine compound include aliphatic polyamine compounds such as hexamethylenediamine, hexamethylenediamine carbamate, and N,N'-dicinnamylidene-1,6-hexanediamine, and aromatic polyamine compounds such as 4,4'-methylenedianiline, m-phenylenediamine, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-(m-phenylenediisopropylidene)dianiline, 4,4'-(p-phenylenediisopropylidene)dianiline, 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminobenzanilide, 4,4'-bis(4-aminophenoxy)biphenyl, m-xylylenediamine, p-xylylenediamine, 1,3,5-benzenetriamine, 1,3,5-benzenetriaminomethyl, and isophthalic acid dihydrazide.
[0057] Examples of polyfunctional epoxy compounds include glycidyl ether type epoxy compounds such as phenol novolac type epoxy compounds, cresol novolac type epoxy compounds, cresol type epoxy compounds, bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, brominated bisphenol A type epoxy compounds, brominated bisphenol F type epoxy compounds, and hydrogenated bisphenol A type epoxy compounds; and other polyfunctional epoxy compounds such as alicyclic epoxy compounds, glycidyl ester type epoxy compounds, glycidyl amine type epoxy compounds, and isocyanurate type epoxy compounds.
[0058] Examples of polyisocyanate compounds include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, hexamethylene diisocyanate, p-phenylene diisocyanate, m-phenylene diisocyanate, 1,5-naphthylene diisocyanate, 1,3,6-hexamethylene triisocyanate, 1,6,11-undecane triisocyanate, and bicycloheptane triisocyanate.
[0059] Examples of the aziridine compound include tris-2,4,6-(1-aziridinyl)-1,3,5-triazine, tris[1-(2-methyl)aziridinyl]phosphinoxide, and hexa[1-(2-methyl)aziridinyl]triphosphatriazine.
[0060] Examples of the sulfur compound include sulfur, 4,4'-dithiomorpholine, tetramethylthiuram disulfide, and tetraethylthiuram disulfide.
[0061] Examples of the thiol compound include 1,3,5-triazinedithiol or a derivative thereof, and 1,3,5-triazinetrithiol.
[0062] Specific examples of higher fatty acid metal salts include lithium salts, sodium salts, potassium salts, and cesium salts of fatty acids having 8 to 18 carbon atoms, such as acetic acid, propionic acid, caproic acid, lauric acid, and stearic acid.
[0063] These crosslinking agents may be used alone or in combination of two or more. The amount of each crosslinking agent is 0.05 to 20 parts by mass, preferably 0.1 to 10 parts by mass, per 100 parts by mass of the acrylic rubber.
[0064] The acrylic rubber-containing composition of the present invention may also contain any of other additives commonly used in the art, such as a lubricant, an antioxidant, a light stabilizer, a filler, a reinforcing agent, a plasticizer, a processing aid, a pigment, a colorant, a crosslinking accelerator, a crosslinking auxiliary, a crosslinking retarder, an antistatic agent, and a foaming agent.
[0065] Examples of the antioxidant include amines, phosphates, quinolines, cresols, phenols, and dithiocarbamate metal salts. Preferred are amines such as diphenylamine derivatives such as 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, and phenylenediamine derivatives.
[0066] Examples of the crosslinking accelerator include guanidine compounds, amine compounds, thiourea compounds, thiazole compounds, sulfenamide compounds, thiuram compounds, and quaternary ammonium salts, with guanidine compounds and amine compounds being preferred.
[0067] Furthermore, it is possible to blend with rubber, resin, etc., as is commonly done in the technical field, without departing from the spirit of the present invention. Examples of rubbers used in the present invention include butadiene rubber, styrene-butadiene rubber, isoprene rubber, natural rubber, acrylonitrile-butadiene rubber, acrylonitrile-butadiene-isoprene rubber, ethylene-propylene-diene rubber, epichlorohydrin rubber, etc., and examples of resins include PMMA (polymethyl methacrylate) resin, PS (polystyrene) resin, PUR (polyurethane) resin, PVC (polyvinyl chloride) resin, EVA (ethylene / vinyl acetate) resin, AS (styrene / acrylonitrile) resin, PE (polyethylene) resin, etc.
[0068] The total amount of the rubber and resin is 50 parts by mass or less, preferably 10 parts by mass or less, and more preferably 1 part by mass or less, per 100 parts by mass of the acrylic rubber of the present invention.
[0069] The method for producing an acrylic rubber-containing composition of the present invention includes a step of blending a crosslinking agent with the acrylic rubber obtained by the above-mentioned method for producing an acrylic rubber.
[0070] The acrylic rubber-containing composition of the present invention can be compounded using any method conventionally used in the field of polymer processing, such as an open roll, a Banbury mixer, or various kneaders.
[0071] The compounding procedure can be the usual procedure used in the field of polymer processing. For example, the polymer alone is first kneaded, then compounding ingredients other than the crosslinking agent and crosslinking accelerator are added to prepare compound A, and then compound B is kneaded by adding the crosslinking agent and crosslinking accelerator.
[0072] The acrylic rubber cross-linked product is obtained by cross-linking the acrylic rubber-containing composition, and the method for producing the acrylic rubber cross-linked product includes a step of cross-linking the acrylic rubber-containing composition obtained by the above-mentioned method for producing the acrylic rubber-containing composition.
[0073] The composition of the present invention can be crosslinked by heating to 100 to 250°C. The crosslinking time varies depending on the temperature, but is usually performed between 0.5 and 300 minutes. Crosslinking molding may be performed in any of the following ways: crosslinking and molding are performed integrally, a previously molded acrylic rubber-containing composition is heated again to form a crosslinked product, and the crosslinked product is heated first and then processed for molding. As a specific method for crosslinking molding, any method such as compression molding using a mold, injection molding, heating using a steam can, air bath, infrared rays, or microwaves can be used.
[0074] Therefore, taking advantage of the above-mentioned properties, the crosslinked product of the present invention can be suitably used as various gaskets, such as O-rings, packings, diaphragms, oil seals, shaft seals, bearing seals, mechanical seals, wellhead seals, seals for electric and electronic devices, seals for pneumatic devices, cylinder head gaskets attached to the joint between a cylinder block and a cylinder head, rocker cover gaskets attached to the joint between a rocker cover and a cylinder head, oil pan gaskets attached to the joint between an oil pan and a cylinder block or a transmission case, gaskets for fuel cell separators attached between a pair of housings sandwiching a unit cell having a positive electrode, an electrolyte plate, and a negative electrode, and gaskets for the top covers of hard disk drives.
[0075] The crosslinked product of the present invention can be used as a rubber material, and is suitably used as an extrusion molded product and a mold crosslinked product for automobile applications, such as various hoses, including fuel oil hoses around fuel tanks, such as fuel hoses, filler neck hoses, vent hoses, vapor hoses, and oil hoses, air hoses, such as turbo air hoses and emission control hoses, radiator hoses, heater hoses, brake hoses, and air conditioner hoses.
[0076] The present invention will be specifically described with reference to examples and comparative examples, although the present invention is not limited thereto.
[0077] In the examples and comparative examples, the polymerization conversion rate and the average particle size of the acrylic emulsion were evaluated.
[0078] [Example 1] (Production of Acrylic Emulsion A) A polymerization reactor equipped with a thermometer, a stirrer, a nitrogen inlet tube, and a pressure reducing device was charged with 60 parts by mass of water, 0.6 parts by mass of polyoxyethylene alkyl ether phosphate sodium salt and 0.16 parts by mass of polyoxyethylene lauryl ether phosphate as emulsifiers, and 19.1 parts by mass of ethyl acrylate, 19.1 parts by mass of n-butyl acrylate, and 0.8 parts by mass of monobutyl fumarate as monomers. After repeated degassing under reduced pressure and nitrogen replacement to sufficiently remove oxygen, 0.054 parts by mass of sodium hydrogensulfite, 0.0001 parts by mass of ferrous sulfate, and 0.03 parts by mass of ammonium persulfate were added to initiate an emulsion polymerization reaction under normal pressure and temperature. The reaction was continued until the polymerization conversion reached 95%, yielding acrylic emulsion A (solids content 40%).
[0079] [Example 2] (Production of acrylic rubber emulsion B) Acrylic Emulsion B (solid content 40%) was obtained in the same manner as for Acrylic Emulsion A, except that the emulsifiers added were changed to 0.4 parts by mass of polyoxyethylene alkyl ether phosphate sodium salt and 0.1 parts by mass of polyoxyethylene lauryl ether phosphate. The viscosity of Acrylic Emulsion B was 13.0 mPa s.
[0080] [Example 3] (Manufacture of acrylic rubber emulsion C) Acrylic Emulsion C (solid content 40%) was obtained in the same manner as for Acrylic Emulsion B, except that the emulsifiers added were changed to 0.2 parts by mass of polyoxyethylene alkyl ether phosphate sodium salt and 0.05 parts by mass of polyoxyethylene lauryl ether phosphate. The viscosity of Acrylic Emulsion C was 8.0 mPa s.
[0081] [Example 4] (Manufacture of acrylic rubber emulsion D) Acrylic Emulsion D (solids content 40%) was obtained in the same manner as in the production of Acrylic Emulsion C, except that the monomers charged were changed to 19.1 parts by mass of ethyl acrylate, 19.1 parts by mass of n-butyl acrylate, and 0.8 parts by mass of vinyl monochloroacetate, the emulsifier was changed to 0.4 parts by mass of polyoxyethylene alkyl ether phosphate sodium salt and 0.05 parts by mass of polyoxyethylene lauryl ether phosphate, and the polymerization secondary material was changed to 0.02 parts by mass of sodium formaldehyde sulfoxylate.
[0082] [Example 5] (Manufacture of acrylic rubber emulsion E) Acrylic Emulsion E (solid content 30%) was obtained in the same manner as in the production of Acrylic Emulsion D, except that the monomers charged were changed to 14.6 parts by mass of ethyl acrylate, 7.3 parts by mass of butyl acrylate, 7.3 parts by mass of methoxyethyl acrylate, and 0.8 parts by mass of vinyl monochloroacetate, and the emulsifiers were changed to 0.13 parts by mass of sodium lauryl sulfate and 0.16 parts by mass of polyoxyethylene alkyl ether.
[0083] [Comparative Example 1] (Manufacture of acrylic rubber emulsion F) Acrylic Emulsion F (solids content 30%) was obtained in the same manner as for Acrylic Emulsion E, except that the amount of water charged was changed to 70 parts by mass, the monomers were changed to 14.7 parts by mass of ethyl acrylate, 14.7 parts by mass of n-butyl acrylate, and 0.6 parts by mass of monobutyl fumarate, the emulsifiers were changed to 0.16 parts by mass of sodium lauryl sulfate and 0.4 parts by mass of polyoxyethylene alkyl ether, and the polymerization secondary material was changed to 0.015 parts by mass of sodium hydrogen sulfite. The viscosity of Acrylic Emulsion F was 5.0 mPa s.
[0084] [Comparative Example 2] (Manufacture of acrylic rubber emulsion G) Acrylic Emulsion G (solid content 40%) was obtained in the same manner as for Acrylic Emulsion E, except that the emulsifiers added were changed to 0.2 parts by mass of polyoxyethylene alkyl ether phosphate sodium salt and 0.023 parts by mass of polyoxyethylene lauryl ether phosphate. The viscosity of Acrylic Emulsion G was 6.0 mPa s.
[0085] (Method for measuring the average particle size of acrylic polymers in acrylic emulsions) The acrylic emulsion was diluted 40 times with ion-exchanged water and measured by dynamic light scattering using a particle size measuring device (Zetasizer Nano S, manufactured by Marvern). The results are shown in Table 1.
[0086] (Method for measuring viscosity of acrylic emulsion) According to JIS K7117-1, the viscosity of the acrylic emulsion was measured in a 23° C. environment using a rotational viscometer (Brookfield, manufactured by Eiko Seiki Co., Ltd.) with an LV-1 spindle at a rotation speed of 30 rpm.
[0087] (Acrylic emulsion stability) The stability of the acrylic emulsion was evaluated according to the following criteria, and the results are shown in Table 1. ◯: The acrylic emulsion after polymerization was left to stand for 2 hours, and then filtered through an 80-mesh wire screen. The amount of aggregates was less than 1% by mass based on the total amount of the acrylic emulsion. ×: The acrylic emulsion after polymerization was left to stand for 2 hours, and then filtered through an 80-mesh wire screen. The amount of aggregates was 1% by mass or more based on the total amount of the acrylic emulsion.
[0088] (About the coagulation properties of acrylic emulsion) The solidification properties of the acrylic emulsion were evaluated according to the following criteria, and the results are shown in Table 1. ◯: 6 parts of sodium sulfate was added to 100 parts of water, heated to 85°C, and 100 parts of acrylic emulsion was added dropwise to solidify, after which the polymer yield was 95% by mass or more. (The polymer content obtained as the residue after drying the acrylic emulsion at 110°C was taken as 100% by mass.) ×: 6 parts of sodium sulfate was added to 100 parts of water, heated to 85°C, and 100 parts of acrylic emulsion was added dropwise to solidify, after which the polymer yield was less than 95% by mass. (The polymer content obtained as the residue after drying the acrylic emulsion at 110°C is taken as 100% by mass.)
[0089] [Table 1]
[0090] From Table 1, the acrylic emulsions of the Examples obtained by the manufacturing method of the present invention are excellent in coagulation property and emulsion stability. On the other hand, the acrylic emulsion of Comparative Example 1 is inferior to the Examples in coagulation property, although the emulsion stability is equivalent. Also, in Comparative Example 2, the emulsion stability is inferior to the Examples in coagulation property, although the coagulation property is equivalent. As a result, it was shown that the acrylic emulsions of the Examples are excellent in coagulation property and emulsion stability, compared to the acrylic emulsions of the Comparative Examples. [Industrial Applicability]
[0091] The acrylic emulsion of the present invention is useful because it has excellent coagulation properties and emulsion stability in the production of acrylic rubber, and is an emulsion with excellent stability during liquid transfer in the production process. The acrylic rubber produced using the acrylic emulsion of the present invention can be widely used as a material for rubber products taking advantage of its excellent heat resistance, weather resistance, ozone resistance, and abrasion resistance. In particular, the crosslinked product produced using the acrylic rubber of the present invention is extremely useful for automotive applications such as fuel hoses, air hoses, and tube materials.
Claims
1. An acrylic emulsion for producing acrylic rubber, comprising: The present invention comprises an acrylic polymer which contains a structural unit derived from a (meth)acrylic acid ester and a structural unit derived from an unsaturated monomer having a crosslinking group, and which is an acrylic fine particle having an average particle diameter (D50) corresponding to a cumulative 50% of 150 nm to 300 nm in a volume-based particle size distribution measured by a dynamic light scattering method, The acrylic emulsion, wherein the crosslinking group is at least one selected from the group consisting of a halogen group, an epoxy group, and a carboxy group.
2. A step of coagulating the acrylic emulsion according to claim 1 with a coagulant to obtain a coagulated slurry; A step of obtaining an acrylic rubber by drying the solidified slurry; The method for producing acrylic rubber comprises the steps of:
3. A method for producing an acrylic rubber composition, further comprising the step of blending a crosslinking agent with the acrylic rubber described in claim 2.
4. A method for producing an acrylic rubber cross-linked product, further comprising a step of cross-linking the acrylic rubber composition described in claim 3.
Citation Information
Patent Citations
Styrene and acrylate latex and preparation method and application thereof
CN107778403A
Thermoplastic resin composition excellent in impact resistance and thermal stability
JP1992120167A
Acrylic emulsion composition
JP1999080485A
Latex for re-peelable pressure-sensitive adhesive, re- peelable pressure-sensitive adhesive composition using same and material to be recorded using same
JP2001031938A
Thermoplastic resin composition
JP2004346235A
